EFEKTIVITAS PENAMBAHAN EKSTRAK DAUN KELOR (Moringa oleifera) PADA PAKAN TERHADAP PERCEPATAN KEMATANGAN GONAD UDANG GALAH (Macrobrachium rosenbergii de man) - Hendra Adi Setiawan; Ganjar Adhywirawan Sutarjo; Dony Prasetyo (Universitas Muhammadiyah Malang, 2024)
The reproductive performance of giant freshwater prawn (Macrobrachium rosenbergii) is an important factor determining the success of aquaculture production. One approach to accelerate gonad maturation is through nutritional supplementation using natural ingredients rich in vitamin E, such as moringa leaf (Moringa oleifera) extract. This study aimed to evaluate the effect of moringa leaf extract supplementation in feed on gonad maturation and survival rate of giant freshwater prawn broodstock. The study employed an experimental method using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of different doses of moringa leaf extract in feed, namely 0 mg/kg feed (control), 134 mg/kg feed, 268 mg/kg feed, and 402 mg/kg feed. Broodstock were maintained in aquaria and fed twice daily using the ad satiation method. Observed parameters included gonad maturation level, survival rate, and water quality. The results showed that supplementation of moringa leaf extract influenced gonad maturation of giant freshwater prawn broodstock. The highest gonad maturation percentage was observed in the treatment of 402 mg/kg feed, reaching 30%, while treatments of 134 mg/kg and 268 mg/kg feed each resulted in 10% gonad maturation. No gonad maturation was observed in the control treatment. The highest survival rate was obtained in the control and 134 mg/kg feed treatments (60%), followed by 268 mg/kg feed (50%) and 402 mg/kg feed (40%). Water quality parameters during the study remained within suitable ranges for prawn culture. In conclusion, supplementation of moringa leaf extract at a dose of 402 mg/kg feed was effective in accelerating gonad maturation of giant freshwater prawn broodstock.